A network meta-analysis comparing treatment modalities of short and long implants in the posterior maxilla with insufficient bone height - Yixuan Zhang; Xiaoyue Tang; Yue Zhang; Can Cao (BMC Oral Health)
Abstract Objective Based on the critical role of implant length and placement timing in treatment success, this study aimed to compare clinical outcomes (implant failure, marginal bone loss, biological and mechanical complications) between short implants (4–8 mm) versus long implants (≥ 8 mm) with sinus floor elevation, and between delayed versus immediate placement of long implants in the posterior maxilla. Methods This network meta-analysis was prospectively registered in the PROSPERO database (CRD42023495027). Adhering to PRISMA-NMA guidelines, we systematically reviewed eligible studies from January 2014 to November 2024 was conducted across major databases, such as the Cochrane Library, PubMed, Embase, Scopus and Web of Science. The main focus of this NMA was to determine the rate of implant failure, as well as to assess marginal bone loss and the occurrence of biological and mechanical complications related to the implants. Results Data from 17 studies, involving 1,076 patients and 1,751 implants, was collected and examined. Long implants have lower failure rates (OR = 1.26; 95% CI = 0.53, 3.00) and short dental implants showed a trend towards lower biological (OR = 0.47; 95% CI = 0.19, 1.18) and mechanical (OR = 0.94; 95% CI = 0.45, 1.94) complications rates, although this trend was not statistically significant. Additionally, compared to longer implants, short implants resulted in a significant reduction in marginal bone loss, regardless of whether long implants were immediately (MD=-0.17; 95%CI: -0.29, -0.05) or delayed (MD = 0.35; 95%CI: 0.05, 0.64) placed following sinus floor elevation. The analysis of cumulative ranking probabilities revealed that delayed placement of long implants with SFE demonstrated the highest efficacy in reducing implant failure (73.9%). SIs were found to excel in reducing marginal bone loss (88.7%) and biological complications (88.2%%), while short implants with SFE proved to be the most effective in preventing mechanical complications (66.0%%). Conclusion Short implants achieved comparable clinical outcomes to long implants with sinus floor elevation in posterior maxilla with limited vertical bone height. Given the limitations of the network meta-analysis and included studies, treatment selection should be individualized based on specific patient conditions.